MANAJEMEN DAN PENDUKUNG SISTEM BIMBINGAN PESERTA DIDIK DI SD NEGERI WOLIBANG - Henderina Womakal; Marsalina Malaikari, Lodia Kamengko, Lea Priska Adangdjaha, Yessy Mata, Petrus Mau Tellu Dony, Anton (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
The purpose of this study is to find out how the structure of the guidance program is implemented in schools and what forms of guidance services are provided by teachers to students at Wolibang State Elementary School. In this interview, the researcher used a qualitative method. Data analysis techniques were carried out by data reduction, data presentation and drawing conclusions. This interview was conducted in Kabola Village, Kabola District. The results of the interview showed that: the guidance program at Wolibang State Elementary School, class III homeroom teachers were directly involved in educating and teaching the students. And the development of the guidance program at Wolibang State Elementary School, class III homeroom teachers provided personal guidance to each student in the form of stages. The homeroom teachers carried out this guidance program structure for the following reasons: (1) the school does not have a guidance teacher so that the class teacher is directly involved in guiding and teaching students (2) Students have different characters due to the influence of environmental and individual factors so that teachers need to provide such guidance (3) the school does not have a guidance program because it uses a high school building, and for the guidance program it is not carried out at all.